Absence of metabolic effects of the topical carbonic anhydrase inhibitors MK-927 and sezolamide during two-week ocular administration to normal subjects - Buclin, T; Biollaz, J; Lippa, E A; Brunner-Ferber, F; van Melle, G; Munafo, A; Clineschmidt, C; Schelling, J L (Clinical pharmacology and therapeutics, 1991)
Potential systemic effects of the racemic carbonic anhydrase inhibitor MK-927 and its S-enantiomer, sezolamide hydrochloride, after topical ocular administration were investigated in a double-masked, randomized, placebo-controlled study in 16 healthy volunteers. A controlled diet was started 4 days before initiation of treatment and continued throughout the study. For 14 days six volunteers received bilaterally one drop of 2% MK-927 (1.2 mg) q.i.d., six received one drop of 1.8% sezolamide (1.1 mg) q.i.d., and four received the common vehicle q.i.d. Blood and urine electrolytes and acid-base profiles were measured before and on days 1, 7, and 14 of treatment, and 24-hour urine samples were collected daily. All values were compared with those on the pretreatment day. Taking the circadian variations of the parameters into account, no significant treatment effect was observed in either the daily profiles or the 14-day cumulative sodium, potassium, and citrate excretions. Because the usual variability of the measured biologic parameters has been reduced markedly by the stringent requirements of this study, it can be concluded that the induction of clinically significant metabolic changes by topically administered MK-927 or sezolamide is unlikely.